2018
DOI: 10.1016/j.jgr.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and anti-inflammatory effects of ginsenoside Rf in a rat model of incisional pain

Abstract: BackgroundGinseng saponin has long been used as a traditional Asian medicine and is known to be effective in treating various kinds of pain. Ginsenoside Rf is one of the biologically active saponins found in ginseng. We evaluated ginsenoside Rf’s antinociceptive and anti-inflammatory effects, and its mechanism of action on adrenergic and serotonergic receptors, in an incisional pain model.MethodsMechanical hyperalgesia was induced via plantar incision in rats followed by intraperitoneal administration of incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…Pronociceptive IL‐1β and IL‐18 are two members of IL‐1 family, and their activity can be blocked by to their specific antagonists IL‐1RA and IL‐18 BP (anti‐inflammatory factors), respectively (Pilat et al, ; Samarani et al, ). We showed that CCI induced upregulation of IL‐1β, IL‐18, and IL‐6 in both the spinal cord and the DRG, which is consistent with previous studies (M. K. Kim et al, ; Sommer et al, ; Wolf et al, ). Previous findings indicate that IL‐10 and other anti‐inflammatory factors are not naturally produced under neuropathic pain conditions (Gonzalez et al, ; Ledeboer et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Pronociceptive IL‐1β and IL‐18 are two members of IL‐1 family, and their activity can be blocked by to their specific antagonists IL‐1RA and IL‐18 BP (anti‐inflammatory factors), respectively (Pilat et al, ; Samarani et al, ). We showed that CCI induced upregulation of IL‐1β, IL‐18, and IL‐6 in both the spinal cord and the DRG, which is consistent with previous studies (M. K. Kim et al, ; Sommer et al, ; Wolf et al, ). Previous findings indicate that IL‐10 and other anti‐inflammatory factors are not naturally produced under neuropathic pain conditions (Gonzalez et al, ; Ledeboer et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that ginsenoside Rf significantly reduced IL‐1β and IL‐6 in both the spinal cord and the DRG. These findings were in line with a previous study showing that ginsenoside Rf restored the elevated IL‐1β and IL‐6 in an acute pain rat model with plantar incision (M. K. Kim et al, ). We also observed decreased protein level of IL‐18 in the DRG but not in the spinal cord of CCI rats after chronic treatment of ginsenoside Rf (Figure b,d).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations